LASERTECHNOLOGY IN MODERN FASHION DESIGN - Fetjko, Ilze; Mežinska, Silvija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2018)
The aim of the article is to explore the available information related to the use of laser technology in the development of modern fashion design. The laser is not only a mechanical instrument, but also a tool for design creation. The relationship between fashion and technology is not new. Laser cutting is increasingly common in garment manufacturing. In synthetic fabrics, laser cutting produces well–finished edges as the laser melts and fuses the edge. In laser engraving laser is used to mark or engrave an object. The marks produced by laser engraving are clean, crisp, permanent. Laser can also be used in marking on various surfaces. The advantages of laser marking is fast, high precision and clear marking on products. Laser marking is durable and can be applied in clothing and leather. Laser marking is considered to be the best choice for branded clothing and marking fashion accessories. In the result of research is one experiment result where the optimal parameters for laser marked artificial silk are shown. In the result of this experiment we can see the most suitable CO2 laser parametres for this fabric.